2016
DOI: 10.1016/j.tjog.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of paternal duplication of 11p15.5→14.3: Its implication of Beckwith–Wiedemann syndrome

Abstract: We presented a prenatally detected chromosomal aberration characterized by paternal duplication of chromosome 11p15.5, which strongly related to the phenotypic manifestation of BWS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The location and extent of the isolated de novo 11p15.1–p15.5 duplication in our patient is depicted with a gray box. Four additional patients from the literature with unbalanced translocations are displayed with black boxes (a–d) : (a) Case ID 4247 of the ECARUCA database with duplication 11p15-pter ( http://ecaruca.radboudumc.nl ); (b) Chen et al 11p14.3-p15.5 [ 13 ]; (c) Turleau et al 11p14-pter [ 11 ]; (d) Fryns et al 11p11-pter [ 12 ]. The ideogram is modified from UCSC genome browser.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The location and extent of the isolated de novo 11p15.1–p15.5 duplication in our patient is depicted with a gray box. Four additional patients from the literature with unbalanced translocations are displayed with black boxes (a–d) : (a) Case ID 4247 of the ECARUCA database with duplication 11p15-pter ( http://ecaruca.radboudumc.nl ); (b) Chen et al 11p14.3-p15.5 [ 13 ]; (c) Turleau et al 11p14-pter [ 11 ]; (d) Fryns et al 11p11-pter [ 12 ]. The ideogram is modified from UCSC genome browser.…”
Section: Discussionmentioning
confidence: 99%
“…Karyotyping revealed an unbalanced translocation 46,XY,der(2)t(2;11)(p25;p15)pat. Finally, Chen et al [ 13 ] recently reported a male fetus with overgrowth, enlarged placenta and CDH leading to a prenatal diagnosis of BWS. Conventional karyotyping revealed the finding of 46,XY,add(11)(q24.2)dn that was refined by array CGH to a 25 Mb duplication of 11p15.5p14.3 including the BWS/SRSCR and a 5.3 Mb deletion of 11q24.3q25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of literature found six reports with known size of paternally derived duplications involving in BWS [ 6 , 9 , 14 , 21 23 ]. The duplication segments ranged in size from 0.3 Mb to 25 Mb (Fig.…”
Section: Discussionmentioning
confidence: 99%